Indian Corporate Bond Market: An Analysis of Growth and Impact of Macroeconomic Determinants. Issue 3 (September 2019) - Neemey, Pooja; Sahay, Namita
Robust, deep and vibrant corporate bond markets are necessary to increase financial system stability of a nation, help the needs of credit and mitigate financial crises of corporate sector that is important for the economic growth. The present article focuses on Indian corporate bond market growth and its impact on some select monetary, fiscal and economic variables as this creates advantages for investors, corporates and governments from 2006–2007 to 2016–2017. The study used the secondary data collection method with the help of monetary, fiscal and economic variables as independent variables and yield rate as dependent variables. From the analysis, it was identified that a complete corporate bond market is associated with economic, monetary and fiscal variables neither negatively nor positively nor at a significant rate. The result of the analysis concludes that among all the selected variables, GDP in percentage is considered as the chief variable that is predominantly mandatory for India because it is commencing its bond market with the foreign participants.